AN ISLAMIC SEARCH OF NOBLE VALUES: THE PREVALENCE OF MODERN PRINCIPLES AND THE RESILIENCE OF LOCAL TRADITIONS IN INDONESIAN DA‘WA - Peter Suwarno (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
The variety of da‘wa (Islamic preaching) in Indonesia indicated not only the diversity in Islamic groups and identities, but also the varieties and changes in values and principles embraced by Indonesian Muslims. This paper argued that these da‘wa activities constitute searches of most suitable Indonesian Islamic principles that inevitably include the negotiation of Islamic, global, and local values. For this purpose, this paper showed examples of various international and Indonesian Islamic scholars and leaders who help change social, political, and religious rhetorical landscape through various arguments involving especially Islamic and modern-international values. This paper maintained that, in addition to Muslims exposure to modern global principles such as democracy and human rights, the increasing popularity and resilience of local-traditional rituals, performances, and expressions in Indonesian da‘wa have significantly shaped the search of the Indonesian Islamic noble values.